Polyimides from 2, 5-bis[4-(4-aminophenoxy)benzoyl]furan and their thermal crosslinking reaction. (March 2022) - Ma, Kai; Jiang, Hanzhou; Chen, Guofei; Wang, Wei; Zhang, Yonggang
Several polyimides were prepared via two-step polycondensation from novel 2, 5-furandicarboxylic acid–based diamine, 2, 5-bis[4-(4-aminophenoxy)benzoyl]furan, with commercial dianhydrides. The chemical structures of the monomers and polymers were characterized by FT-IR and NMR in detail, respectively. The polyimides exhibited high performances with 5 wt% weight loss temperatures of over 410 o C, glass transition temperatures of over 214 o C, and tensile strengths and Young's moduli of up to 130 MPa and 3.2 GPa, respectively. The thermal crosslinking mechanism was studied by FT-IR, Raman spectroscopy, and model reaction analysis, which showed the Diels–Alder reaction between the furan group and diphenylethylene group was the main reaction. The crosslinked polyimide films showed improved solvent resistance, and thermal and mechanical properties.